2010
DOI: 10.1111/j.1751-7176.2010.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Insulin Sensitivity and Muscle Blood Flow in Aerobic‐Trained Overweight‐Obese Hypertensive Patients Are Not Associated With Ambulatory Blood Pressure

Abstract: To verify whether there are relationships between vascular and hormonal responses to aerobic training in hypertensive persons, sedentary hypertensive patients were randomized to an aerobic training or a callisthenic exercise group. The patients' 24-hour blood pressure, arterial compliance, forearm blood flow, and hormonal profile were evaluated at baseline and after 3-month training protocols. Mean maximal oxygen consumption (VO 2 max) increased by 8% in the aerobic group (P<.001), while no change was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 39 publications
1
21
0
1
Order By: Relevance
“…Changes in plasma aldosterone and cortisol could also be involved in blood pressure regulation during aerobic training. Neuro-hormonal and vascular adaptations are also potential mechanisms that could explain blood pressure lowering effect of endurance training in hypertension [37]. The results of the current study were confirmed by Aoike DT et al The decrease in blood pressure due to mild/moderate aerobic exercise has been well established both in normotensive and hypertensive individuals as well as in chronic kidney disease patients.…”
Section: Discussionsupporting
confidence: 85%
“…Changes in plasma aldosterone and cortisol could also be involved in blood pressure regulation during aerobic training. Neuro-hormonal and vascular adaptations are also potential mechanisms that could explain blood pressure lowering effect of endurance training in hypertension [37]. The results of the current study were confirmed by Aoike DT et al The decrease in blood pressure due to mild/moderate aerobic exercise has been well established both in normotensive and hypertensive individuals as well as in chronic kidney disease patients.…”
Section: Discussionsupporting
confidence: 85%
“…The trials were conducted between 1988 and 2012. Four studies were conducted in Europe [13,22,24,25], three in the USA [15,17,19], four in South America [11,12,16,23], three in Asia [18,20,21] and one in Australia [14]. Twelve trials had a parallel design and the remaining three used a cross-over design [18,22,25].…”
Section: Trial and Participant Characteristicsmentioning
confidence: 99%
“…The percentage of dropouts ranged from 0 to 38% in the exercise group and between 0 and 35% in the control group, so that a total of 633 participants could be included in the final analysis (394 exercise participants and 239 control participants). Five trials included only men [14,15,18,22,25], two studies were restricted to women only [11,12] while the remaining eight trials [13,16,17,[19][20][21]23,24] included both men and women. In the final analysis, 301 participants were men, 246 women and 86 unknown sex [13].…”
Section: Trial and Participant Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations